Influence of Spark Plasma Sintering and Baghdadite Powder on Mechanical Properties of Hydroxyapatite - Khandan, A.; Karamian, E.; Mehdikhani-Nahrkhalaji, M.; Mirmohammadi, H.; Farzadi, A.; Ozada, N.; Zamani, K. (Elsevier Science Bv, 2015)
Since hydroxyapatite-based materials have similar composition and crystallinity as natural calcified tissues, can be used for bone/tissue engineering. In the present study a novel nanocomposite based on bioceramics such as Natural Hydroxyapatite (NHA) and Baghdadite (BAG), was sintered by spark plasma sintering (SPS) technique. The prepared composite was characterized using scanning electron microscopy (SEM), X-ray diffractometer (XRD) and Brunauer Emmett Teller (BET) techniques. The porosity of the samples was measured by Archimedes method. The cold crushing strength (CCS) test was applied to evaluate their mechanical properties. Our results demonstrated that NHA-30wt. %BAG nanocomposite specimens have the lower CCS in comparison with other examined composites. Consequently, NHA/BAG samples exhibited acceptable mechanical properties and could be suitable candidates for bone tissue engineering applications especially orthopaedic fields. (C) 2015 The Authors. Published by Elsevier Ltd.
5th International Biennial Conference on Ultrafine Grained and Nanostructured Materials, UFGNSM15 -- NOV 11-12, 2015 -- Tehran, IRAN
Keywords: Baghdadite; Natural hydroxyapatite; Nanocomposite; Spark Plasma Sintering; Tissue Engineering